The effect of silanated and impregnated fiber on the tensile strength of E-glass fiber reinforced composite retainer - Niswati Fathmah Rosyida; Siti Sunarintyas; Pinandi Sri Pudyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Fiber reinforced composite (FRC) is can be used in dentistry as an orthodontic retainer. FRC still has a limitations because of to a weak bonding between fibers and matrix. Purpose: This research was aimed to evaluate the effect of silane as coupling agent and fiber impregnation on the tensile strength of E-glass FRC. Methods: The samples of this research were classified into two groups each of which consisted of three subgroups, namely the impregnated fiber group (original, 1x addition of silane, 2x addition of silane) and the non-impregnated fiber group (original, 1x addition of silane, 2x addition of silane). The tensile strength was measured by a universal testing machine. The averages of the tensile strength in all groups then were compared by using Kruskal Wallis and Mann Whitney post hoc tests. Results: The averages of the tensile strength (MPa) in the impregnated fiber group can be known as follow; original impregnated fiber (26.60±0.51), 1x addition of silane (43.38±4.42), and 2x addition of silane (36.22±7.23). The averages of tensile strength (MPa) in the non-impregnated fiber group can also be known as follow; original non-impregnated fiber (29.38±1.08), 1x addition of silane (29.38±1.08), 2x addition of silane (12.48±2.37). Kruskal Wallis test showed that there was a significant difference between the impregnated fiber group and the non-impregnated fiber group (p<0.05). Based on the results of post hoc test, it is also known that the addition of silane in the impregnated fiber group had a significant effect on the increasing of the tensile strength of E-glass FRC (p<0.05), while the addition of silane in the non-impregnated fiber group had a significant effect on the decreasing of the tensile strength of E-glass FRC. Conclusion: It can be concluded that the addition of silane in the non-silanated fiber group can increase the tensile strength of E-glass FRC, but the addition of silane in the silanated fiber group can decrease the tensile strength of E-glass FRC. It is also known that the impregnation of fiber can increase the tensile strength of E-glass FRC.